Pre- and Post-harvest Factors Affecting Glucosinolate Content in Broccoli - Ilahy, Riadh; Tlili, Imen; Pék, Zoltán; Montefusco, Anna; Siddiqui, Mohammed Wasim; Homa, Fozia; Hdider, Chafik; R'Him, Thouraya; Lajos, Helyes; Lenucci, Marcello Salvatore (Frontiers in Nutrition, 2020)
Owing to the several presumed health-promoting biological activities, an increasing attention is being given to plant natural chemicals, especially those frequently entering the human diet. Glucosinolates (GLs) are the main bioactive compounds found in broccoli (Brassica oleracea L. var. italica Plenck). Their regular dietary assumption has been correlated with reduced risk of various types of neoplasms (lung, colon, pancreatic, breast, bladder and prostate cancers), some degenerative diseases such as Alzheimer, as well as decreased incidence of cardiovascular pathologies. GLs synthesis pathway and regulation mechanism have been elucidated mainly in Arabidopsis. However, nearly 56 putative genes have been identified as involved in B. oleracea GLs pathway. It is widely recognized that, there are several pre-harvest (genotype, growing environment, cultural practices, ripening stage, etc.) and post-harvest (harvesting, post-harvest treatments, packaging, storage, etc.) factors that affect GLs synthesis, profiles and levels in broccoli. Understanding how these factors act and interact in driving GLs accumulation in the edible parts is essential for developing new broccoli cultivars with improved functional quality. In this regard, any systematic and comprehensive review outlining the effects of pre- and post-harvest factors on the accumulation of GLs in broccoli is not yet available. Thus, the venture of this paper is to fill this gap giving a synoptic overview of the most relevant and recent literature.